Citizen Science for Quantification of Insect Abundance on Windshields of Cars Across Two Continents - Møller, Anders Pape; Czeszczewik, Dorota; Erritzøe, Johannes; Flensted-Jensen, Einar; Laursen, Karsten; Liang, Wei; Walankiewicz, Wiesław (Frontiers in Ecology and Evolution, 2021)
The abundance and the diversity of insects in Europe have declined considerably during recent decades, while it remains unclear whether similar changes may also have occurred elsewhere. Here we used citizen science for quantifying the abundance of flying insects on windshields of cars across Europe and to a smaller extent in China. We used the abundance of insects killed against windshields of cars during 3,530 transects for a total distance of 83,019 km made by 50 observers as estimates of insect abundance. A total of 124,606 insects were recorded, or approximately 1.5 insect per km. The abundance of insects killed against windshields was highly repeatable among days for the same locality, showing consistent estimates of abundance. The main determinants of insect abundance were features of cars (driving speed and car model that can be considered noise of no biological significance), local weather (temperature, cloud cover and wind speed) and variation across the season and the day. We tested for differences in the abundance of flying insects killed on windshields of cars predicting and finding (1) a reduction in insect abundance in areas with ionizing radiation at Chernobyl compared to uncontaminated control sites in the neighborhood, (2) a reduction in the abundance of flying insects in Western compared to Eastern Europe, (3) a reduction in the abundance of flying insects killed on windshields from southern to northern Europe compared to latitudinal samples of insects from southern to northern China, and (4) a difference in abundance of insects killed on windshields of cars in Spain with a significant interaction between Spain and Denmark. Thus a number of abiotic and biotic factors accounted for temporal and spatial heterogeneity in abundance of insects, providing a useful tool for monitoring and studying determinants of spatial and temporal patterns of insect abundance. This also implies that our estimate of insect abundance may be relevant for the study of competition and for interactions at higher trophic levels.